FRI0076 Low Disease Activity or DAS-Remission as Treatment Target in Early Rheumatoid Arthritis Patients. (15th July 2016) - Akdemir, G.; Markusse, I.M.; Schouffoer, A.A.; de Sonnaville, P.B.; Grillet, B.A.; Kerstens, P.J.; Lems, W.F.; Huizinga, T.W.; Allaart, C.F.
Abstract : Background: It is unknown what the optimum treatment target for early rheumatoid arthritis (RA) patients is. Objectives: To assess which treatment target, low disease activity or disease activity score (DAS)-remission is more effective in early RA patients. Methods: The BeSt study included early (≤2 years symptom duration) active (≥6 of 66 swollen joints, ≥6 of 68 tender joints, and either erythrocyte sedimentation rate ≥28 mm/hour or a visual analogue scale global health score ≥20mm) RA (1987 criteria) patients to compare 4 treatment strategies, targeted at DAS≤2.4. In arm 3 treatment started with a combination of methotrexate (MTX), sulfasalazine and a tapered high dose of prednisone. In the IMPROVED study, early arthritis patients started with MTX and a tapered high dose of prednisone, with subsequent treatment options aiming at DAS-remission (<1.6). We compared clinical outcomes during 5 years in 133 BeSt patients randomized to arm 3 with 175 IMPROVED patients who fulfilled the inclusion criteria of the BeSt study. Predictive factors for DAS<1.6 at year 1 and drug-free remission (DFR) at year 5 were assessed by logistic regression analysis. Results: At baseline IMPROVED patients had a significantly lower mean±SD DAS compared to BeSt patients (4.1±0.7 vs 4.4±0.9, p=0.012) and a shorter median (IQR) symptom duration (17 (8–28) vs 23 (15–53) weeks, p<0.001) (figure ). At 3 months in the BeSt study, DAS decreased by 2 to 2.4±1.0, functional ability improved from 1.4±0.7 to 0.6±0.6, 56% of patients achieved DAS≤2.4 and 20% were in DAS-remission. At 4 months in IMPROVED patients, DAS decreased >2 to 1.8±1.0, functional ability improved from 1.5±0.6 to 0.5±0.6, 72% of patients achieved DAS≤2.4 and 53% were in DAS-remission. At year 1, DAS was decreased by 2.5 in IMPROVED and 2.4 in BeSt compared to baseline, to 1.6±1.0 and 2.0±0.9, p=0.004, and more IMPROVED patients than BeSt patients had achieved DAS<1.6 (51% vs 30%, p<0.001). Similar percentages in both studies achieved DAS≤2.4 (73% in IMPROVED vs 67% in BeSt, p=0.333). By protocol, BeSt patients could not achieve DFR at year 1. DFR was achieved in 15% of IMPROVED patients. At year 5, DAS was decreased by 2.7 in IMPROVED and 2.6 in BeSt compared to baseline, to 1.5±0.8 and 1.7±0.8, respectively (p=0.014). DAS≤2.4 was achieved in 61% of IMPROVED patients and in 61% of BeSt patients (p=0.092), DAS<1.6 was achieved in 43% vs 32%, p=0.003, and DFR was achieved in 18% vs 8%, p=0.003. Predictive factors for DAS<1.6 at year 1 were type of treatment study (OR for IMPROVED (95% CI) 2.16 (1.27–3.68)), male gender (2.31 (1.34–3.98)) and baseline tender joint count (0.94 (0.90–0.99)). IMPROVED study (3.33 (1.44–7.66)) and absence of RF (rheumatoid factor) and ACPA (anti-citrullinated protein antibodies) 4.24 (1.71–10.51) were predictive factors for DFR at year 5. Conclusions: Although the treatment target was less often achieved for DAS<1.6 compared to DAS≤2.4, irrespective of baseline disease activity, patients with early active RA had better outcomes after DAS<1.6 than DAS≤2.4 targeted therapy. Male gender, low baseline tender joint count and absence of RF and ACPA were also associated with more favourable treatment outcomes. Disclosure of Interest: G. Akdemir: None declared, I. M. Markusse: None declared, A. A. Schouffoer: None declared, P. B. de Sonnaville: None declared, B. A. Grillet: None declared, P. J. Kerstens: None declared, W. F. Lems: None declared, T. W. Huizinga: None declared, C. F. Allaart Grant/research support from: Year 1 of the IMPROVED study was sponsored by Abbott. The BeSt study was designed by the investigators and supported by a government grant from the Dutch Insurance Companies, with additional funding from Schering-Plough B.V. and Janssen B.V. Data collection, trial management, data analysis and preparation of the manuscript were performed by the authors.